Sensorial properties assessment in metallic parts with piezoelectric particles - Caçador, José David Fernandes (2023)
Predictive maintenance through a condition-based continuous monitoring perspective is a predominant matter in Structural Health Monitoring (SHM). This can be achieved by using embedded sensors (ESs) in structures’ metal matrices or through surface sensors (SSs). These last are exposed to external environmental conditions that can be quite severe, damaging sensors and compromising their functionality. For this reason, there has been an increasing interest in researching ESs and their inherent manufacturing processes by the scientific community. These sensors use smart materials to convert external stimuli into electrical output signals. In the last few years, much effort has been dedicated to assess the possibility of incorpo- rating these materials in metal matrix components. However, conventional manufacturing processes are associated with high processing temperatures due to the fusion of base material. For this reason, solid-state processing techniques have been studied to allow the production of smart materials. The Research and Development Unit for Mechanical and Industrial Engineering (UNIDEMI) of NOVA School of Science and Technology used Friction Stir Processing (FSP) for the first time to incorporate piezoelectric particles in a work-hardened alu- minium alloy AA5083-H111, thus creating a self-sensing material. The purpose of this dissertation was to assess the sensorial properties granted to different heat-treated alu- minium alloys, namely AA2017-T451 and AA7075-T651, through the incorporation of Lead Zirconate Titanate (PZT) and Barium Titanium Oxide (BTO) piezoelectric particles, and perform its characterization and comparison between the sensorial properties obtained to AA5083-H111. Experimental results of this endeavour demonstrated that processing with different heat-treated aluminium alloys did not compromise the sensorial behaviour of the SSMs. However, the sensorial characterisation of the produced SSMs revealed that the obtained sensitivities are lower than those obtained for the AA5083-H111.